Inadvertent life-threatening total spinal anesthesia following caudal block in a preschool child underwent urologic surgery: A rare case report. (November 2021) - Sisay, Amanuel; Girma, Betelihem; Negusie, Teklu; Abdi, Sherif; Horsa, Bayisa; Ayele, Kinfe
Abstract: Introduction and importance: Caudal block is considered to be safe and provide optimal analgesia for pediatric patients undergoing sub-umbilical operations. It overcomes opioid-related side effects, particularly the dangers associated with respiratory depression in small children. Case presentation: A 5-year-old male underwent uneventful hypospadias surgery under general endotracheal anesthesia. Caudal block planned to be administered postoperatively for postoperative analgesia then performed after palpation of sacral cornu with 8 ml of 0.25% bupivacaine. A few minutes later, the patient became apneic, heart rate, blood pressure, and oxygen saturation dropped abruptly—immediate resuscitation with ventilatory support, fluid bolus, and atropine administration. After a minute patients' vital signs returned to the normal range then 2 h later patient started to breathe spontaneously and consciousness is regained. After close follow-up for 24 h in the post-anesthesia care unit patient was discharged to the pediatric ward then discharged to home without any neurologic sequelae after 3 days. Clinical discussion: Total spinal anesthesia in a very infrequent incident during central neuraxial blocks, especially in the pediatrics population where a caudal block is usually performed. Manifestation of this event can be detected by loss of consciousness, cessation of respiratory effort, hemodynamic instability, and dilated pupils. Delayed treatment can result in cardiopulmonary arrest. Conclusion: Unanticipated total spinal anesthesia following central neuraxial blocks can potentially cause severe adverse consequences. Preventive modalities must be employed to avoid this incident. Early recognition and instant management should be instituted to avoid dangerous complications following the total spinal blockade. Highlights: Caudal block is a widely used technique to provide anesthesia and analgesia during pediatric surgery. Although it is sporadic, total spinal blockade might result from caudal block Repeated aspiration and use of a needle with stylet should be considered as a precaution to avoid total neuraxial blockade. Quick recognition and immediate management of total spinal is mandatory to avoid serious complications.